Earnings and Capability Requirements - Hartog, Joop (The Review of Economics and Statistics, 1980)
reported here was supported by funds granted to the Institute for Research on Poverty at the University of Wisconsin-Madison by the Department of Health, Education, and Welfare pursuant to the provisions of the Economic Opportunity Act of 1964. The conclusions expressed herein· are those of the author.. f' This paper empirically investigates the relationship between earnings and capability requirements in the United States. Emphasis is on the need to use data on the capability requirements of an individual's job rather than on an individual's capability endowments. Data are taken from the 1950 and 1960 Censuses and from the Dictionary of Occupational Titles (DOT). Using factor analysis, the DOT data are searched for some underlying basic capabilities; next, implicit capability prices are estimated. Non-:-linearity in the earnings function is analyzed, and price changes over time are studied as well.